"I know him!": Does witness-defendant familiarity impact mock jurors across different aged witnesses and types of crime? - Pica, Emily (Applied psychology in criminal justice, 2019)
The current study examined whether eyewitness age (5-, 10-, 15-years-old), eyewitness familiarity with the defendant (personally familiar, casually familiar, stranger), and nature of the crime (personal, non-personal) infl uenced jurors' judgments. Undergraduate students (N = 568) read a case summary where the eyewitness reported being victim to an abduction or victim of a bike theft and were asked to render a dichotomous verdict, continuous guilt rating, and answer questions regarding their perceptions of the defendant and the eyewitness' identification. Familiarity and nature of the crime interacted to infl uence guilt ratings, perceptions of the defendant, and perceptions of the eyewitness' identification. Jurors reported higher guilt ratings, lower perceptions of the defendant, and were more likely to believe the eyewitness' identification was accurate when the eyewitness and defendant were familiar with each other and the crime was personal compared to nonpersonal. These results suggest familiarity between witnesses and defendants can infl uence